The Cyprian genus Exodrymadusa Karabag (Orthoptera: Tettigoniidae) - Ünal, Mustafa (Zootaxa, 2008)
The Cyprian endemic genus Exodrymadusa Karaba™ is studied. First male of only known species Exodrymadusa inornata Uvarov is described. Taxonomic position of the genus is discussed. Descriptive illustrations are given.